2003
DOI: 10.1210/me.2002-0438
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cell-Derived Factor 1, a Novel Target of Estrogen Receptor Action, Mediates the Mitogenic Effects of Estradiol in Ovarian and Breast Cancer Cells

Abstract: Recent clinical studies estimate that 60-70% of human ovarian and breast cancers overexpress the estrogen receptor (ER). However, despite the established mitogenic effects of estrogen in these tumors, proliferative markers of hormone action are limited. In the current study, we report that the growth stimulatory cytokine stromal cell-derived factor 1 (SDF-1) is a bona fide target of estrogen action in ERalpha-positive human ovarian and breast cancer cells. Notably, estradiol treatment of BG-1 (ovarian carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
188
4
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(212 citation statements)
references
References 44 publications
14
188
4
6
Order By: Relevance
“…Several previously known ERa-regulated genes were detected in this study, for example, TFF1/pS2 (FC 34.8), GREB1 (FC B8 for three transcript variants), SIAH 2 (FC 5.3), SDF1/CXCL12 (FC 5.6), IGFBP-4 (FC 5.5), CCNA2 (FC 4.2), STC2 (FC 2.3), PR (FC 1.9), RBBP-8 (FC 1.7), NRIP1/RIP140 (FC 1.7), CTSD (FC 1.6) and NR5A2/LRH1 (FC 1.7), all confirming the data previously published (Roberts et al, 1988;Inoue et al, 2002;Hall and Korach, 2003;Annicotte et al, 2005;Frasor et al, 2005). Also downregulated genes such as ERa itself (FC 0. by ERa and decrease of S100A6/calcyclin by ERb correlates to the earlier findings of in vivo gene expression in wt and ER knockout mouse bone tissue (Lindberg et al, 2003).…”
Section: Comparisons With Literaturesupporting
confidence: 88%
“…Several previously known ERa-regulated genes were detected in this study, for example, TFF1/pS2 (FC 34.8), GREB1 (FC B8 for three transcript variants), SIAH 2 (FC 5.3), SDF1/CXCL12 (FC 5.6), IGFBP-4 (FC 5.5), CCNA2 (FC 4.2), STC2 (FC 2.3), PR (FC 1.9), RBBP-8 (FC 1.7), NRIP1/RIP140 (FC 1.7), CTSD (FC 1.6) and NR5A2/LRH1 (FC 1.7), all confirming the data previously published (Roberts et al, 1988;Inoue et al, 2002;Hall and Korach, 2003;Annicotte et al, 2005;Frasor et al, 2005). Also downregulated genes such as ERa itself (FC 0. by ERa and decrease of S100A6/calcyclin by ERb correlates to the earlier findings of in vivo gene expression in wt and ER knockout mouse bone tissue (Lindberg et al, 2003).…”
Section: Comparisons With Literaturesupporting
confidence: 88%
“…Supporting this notion, it has been recently reported that several CXCR4 þ cancers (e.g., breast, ovarian, prostate cancers, as well as rhabdomyosarcoma and neuroblastoma) metastasize to the bones and lymph nodes in an SDF-1-dependent manner. [55][56][57][58][59] As mentioned, CXCR4 is also expressed on cells from several hematopoietic malignancies. For example, the SDF-1-CXCR4 axis is responsible for retention in BM of acute lymphoid leukemia and acute myeloid leukemia (AML) cells.…”
Section: Cancer Cells Express Cxcr4mentioning
confidence: 91%
“…15,22,23 Moreover, Murakami et al 14 reported that in a murine in vivo model, CXCR4-transfected melanoma cells demonstrated a marked increase in pulmonary metastasis compared to mock cells after i.v. and s.c. inoculation of tumor cells.…”
Section: Functional Analysis Of Cd26/dppiv In Emca Cells In Vitromentioning
confidence: 99%